PREVALENCE OF MARKERS OF VIRAL HEPATITIS B AND D FROM HEALTHY POPULATION IN REPUBLIC TYVA - T. Kozhanova V.; L. Ilchenko Yu.; V. Klushkina V.; M. Lopatukhina A.; E. Amon P.; A. Saryglar A.; O. Isaeva V.; K. Kyuregyan K.; M. Michailov I.; Т. Кожанова В.; Л. Ильченко Ю.; В. Клушкина В.; et al. (Association of Pediatricians and Infection Disease doctors, LLC "Diagnostics and Vaccines", 2015)
Aim: to estimate prevalence of markers, genetic diversity, risk factors of HBV and HDV infections in all age groups among healthy population in Republic Tyva. Serum samples obtained from healthy population in Republic Tyva (N = 1086) were tested (aged from birth to older 60 years). The markers of HBV and HDV infections were determined by enzyme immunoassay and PCR. HBsAg was detected in 7,7% (84/1086), anti-HBc — in 47,8% (519/1086) and HBeAg — in 0,3% (3/1086) cases. Prevalence of HBsAg in children under 9 years was 1,3%, no positive results of anti-HDV were determined among children aged up to 9 year. Prevalence of anti-HDV among HBsAg-positive individuals of healthy population was 32,1% (27/84). HBV DNA was detected in 2,9% (31/1086) cases; HDV RNA — in 32,1% (14/84) HBsAg-positive individuals. The obtained data showed high prevalence of HBV ang HDV infections among healthy population of Republic Tyva. Thus, it is necessary to extend screening program in this region to improve viral hepatitis surveillance and diagnostics. The sharp decline in the prevalence of these infections in children up to 9 years in the surveyed endemic region is an evidence of effective protection against HBV and HDV with vaccination against hepatitis B. Цель работы: оценить распространенность маркеров, генетическое разнообразие, факторы риска инфицирования вирусами HBV и HDV во всех возрастных группах детского и взрослого условно здорового населения Республики Тыва. Исследованы образцы сывороток крови, полученные от условно здорового населения Республики Тыва (N = 1086), от новорожденных до лиц старше 60 лет. Маркеры инфицирования HBV и HDV определяли методом ИФА и ПЦР. HBsAg был определен в 7,7% (84/1086), anti-HBc — в 47,8% (519/1086) и HBeAg — в 0,3% (3/1086) случаях. Частота выявления anti-HDV среди HBsAg-положительных лиц из группы условно здорового населения составила 32,1% (27/84). HBV DNA была определена в 2,9% (31/1086) случаях; HDV RNA была обнаружена у 32,1% (14/84) HBsAg-положительных лиц. Среди детей до 9 лет частота выявления HBsAg составила 1,3%, в этой возрастной группе не было выявлено ни одного образца сыворотки крови с наличием anti-HDV. Полученные нами данные свидетельствуют о высоком уровне инфицирования HBV и HDV условно здорового населения Республики Тыва, что указывает на необходимость расширения скрининговых программ в данном регионе для усовершенствования диагностики вирусных гепатитов и надзора за этими инфекциями. Резкое снижение распространенности данных инфекций среди детей до 9 лет в обследованном эндемичном регионе является свидетельством эффективной защиты от HBV и HDV с помощью вакцинации против гепатита В.